Implementation of confirmatory factor analysis: a measuring model of reading academic achievement - Fernández Aráuz, Andrés (2015)
The aim of this paper is to show the differences between exploratory and confirmatory factor analysis. The results obtained with confirmatory factor analysis show that both education and socioeconomic status of the parents of students, as well as material possessions at home are good indicators to measure the latent variable called Socioeconomic Extraction. Moreover, the enjoyment of reading and diversity of reading are good indicators of measurement for the latent variable Personal Attitude of the student, while the student's attitude towards school, which measure attitudes to educational process as a whole and not specifically to the reading is not a good measure for the latent variable of personal attitude. These results suggest that unobservable factors Socioeconomic Extraction, Reading Strategies and personal attitude could be used to assess the causal hypothesis of the effect of these variables on the educational performance of students in the reading test.